HASIL JADI BORDIR DENGAN MENGGUNAKAN KAIN VELVET MENGGUNAKAN MESIN BORDIR JUKY DI SURABAYA (BUGARIS, 2024)
This research is motivated by the fact that decorate fabric with embroidery because it feels more practical, the fabric often used is cloth embroidered Cotton because it is easy, but the clothing, accessories and household linen also uses fabrics that sparkle like Velvet fabric. The statements of the problem is how the influence of Velvet material types to the result of embroidery using Juky embroidery machine? The is purpose of the study to describe the influence of Velvet material types to the result of embroidery using Juky embroidery machine. The significance of the study is to obtain research results, as references and literature sources PKK majors in University of PGRI Adi Buana Surabaya and embroidery entrepreneurs. Velvet fabric has a surface characteristics of the fabrics soft and shiny. Embroider is embroidering fabrics with yarn engineering and special machine embroidery such as Juky embroidery machine namely high-speed machines. This research is a deckriftive quantitative the data analysis is using statistical techniques percentace (%). Using data collection is experimental, observation and questionnaires. The research sample is 15 respondents were selected at is random sampling and 5 respondents who are experts in the field of embroidery. The results showed that the Velvet material types influentials to the result of embroidery using Juky embroidery machine with a percentace is 3.8%. Velvet material types influential on stitching of embroidery is very neat, nice, flat, stable, almost no holes. The Velvet fabric surface after embroidered slightly bubbly. The Velvet fabric increasingly looks beautiful and fit embroidered. The results of this study are useful as a reference for the development of variety of embroidery for embroidery companies, as a reference to the PKK – fashion majors in embroidery subjects as literature sources for The University of PGRI Adi Buana Surabaya.